Why We Need an Engaged Interreligious Theology. Issue 2 (9th October 2018) - Schmidt-Leukel, Perry
Abstract : In contrast to various recent trends, this paper understands the engagement in "engaged interreligious theology" primarily as an engagement with the various religious truth claims. The overall goal of such engagement is not defined in terms of political or practical commitment but as the search for truth. Although the question of how the religions assess the salvific potential of other faiths and the compatibility or incompatibility of their respective beliefs has significant political implications, the paper argues that political or ideological interest must not take precedence over an open inquiry into truth according to the general standards of academic scholarship.